ARCHIGESH 24. Buffoonery / Cardboard Country - Олег Голубев; Валентина Носова (Проект Байкал, 2024)
The article describes the features of the Festival of Architects-Mountain Skiers 2024. It provides information about the participants of sports competitions, competitive-educational and entertaining-creative programmes. The authors emphasize that the importance of the professional component of the festival becomes more serious and diverse.